2005
DOI: 10.1002/jcb.20485
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of regucalcin suppresses cell death and apoptosis in cloned rat hepatoma H4‐II‐E cells induced by insulin or insulin‐like growth factor‐I

Abstract: The role of regucalcin, a regulatory protein in intracellular signaling pathway, in cell death was investigated by using the cloned rat hepatoma H4-II-E cells overexpressing regucalcin. The hepatoma cells (wild-type) and stable regucalcin/pCXN2 transfectants were cultured for 72 h in a medium containing 10% fetal bovine serum (FBS) to obtain subconfluent monolayers. After culture for 72 h, cells were further cultured for 24-72 h in a medium containing either vehicle, insulin (10(-8) or 10(-7) M) or insulin-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Regucalcin is a calcium-binding protein, which regulates the calcium effects on liver cell functions, modulates lipid metabolism in the adipose and liver tissues in aging rats by interacting with leptin or adiponectin, and suppresses apoptotic cell death [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Regucalcin is a calcium-binding protein, which regulates the calcium effects on liver cell functions, modulates lipid metabolism in the adipose and liver tissues in aging rats by interacting with leptin or adiponectin, and suppresses apoptotic cell death [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…H4-II-E cells were cultured in a medium containing, either vehicle, insulin, IGF-I, epinephrine, or transforming growth factor-β (TGF-β) in absence of FBS [50]. The number of wild-type cells was decreased after culture of insulin or IGF-I [50].…”
Section: Regucalcin Suppresses Apoptosis In Modeled Liver Cellsmentioning
confidence: 99%
“…H4-II-E cells were cultured in a medium containing, either vehicle, insulin, IGF-I, epinephrine, or transforming growth factor-β (TGF-β) in absence of FBS [50]. The number of wild-type cells was decreased after culture of insulin or IGF-I [50]. Agarose gel electrophoresis showed presence of low-molecular-weight DNA fragments of adherent wild-type cells cultured in the presene of insulin or IGF-I [36].…”
Section: Regucalcin Suppresses Apoptosis In Modeled Liver Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, regucalcin increased superoxide dismutase activity in the heart of normal and regucalcin transgenic animal models [75]. Recently, it has been reported that overexpression of regucalcin could suppress apoptosis in rat hepatoma cells induced by various signaling pathways [76]. Regucalcin may directly activate cysteinyl proteases including Ca 2+ -dependent protease calpain, which could be responsible for APP processing [77].…”
Section: Chemical Genetic Approach To Under-standing Mechanisms Of Brmentioning
confidence: 98%